Descriptive Inorganic Chemistry Researches of Metal Compounds - Akitsu, Takashiro (IntechOpen, 2017)
Metal ions play an important role in analytical chemistry, organometallic chemistry, bioinorganic chemistry, and materials chemistry. This book, Descriptive Inorganic Chemistry Researches of Metal Compounds, collects research articles, review articles, and tutorial description about metal compounds. To perspective contemporary researches of inorganic chemistry widely, the kinds of metal elements (typical and transition metals including rare earth; p, d, f-blocks) and compounds (molecular coordination compounds, ionic solid materials, or natural metalloenzyme) or simple substance (bulk, clusters, or alloys) to be focused are not limited. In this way, review chapters of current researches are collected in this book.